CLINICOPATHOLOGICAL STUDY OF NON-NEOPLASTIC LESIONS OF NASAL CAVITY AND PARANASAL SINUSES IN A TERTIARY CARE TEACHING HOSPITAL - SAINI, SWATI; Badyal, Rama Kumari; SINGH, HARPAL; BHAGAT, SANJEEV (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: A variety of non-neoplastic lesions involving the nasal cavity (NC) and paranasal sinuses (PNS) are encountered in clinical practice. The clinical features, symptoms, and advanced imaging technique help to reach a provisional diagnosis but histopathological examination remains the mainstay of final definitive diagnosis. There is a lack of studies that exclusively cover non-neoplastic lesions of sinonasal region. Hence, this study was done with the aim of examining the clinicopathological features of various non-neoplastic lesions of NC and PNS. Methods: The formalin-fixed specimens of polypectomy/biopsy were received with complete clinical and radiological features in the department of pathology. Routine gross examination and required number of sections were taken and stained with hematoxylin and eosin stain. Periodic acid Schiff’s was used wherever necessary. Results: Histologically, maximum number of cases were of inflammatory polyp (IP) (57%), followed by Allergic polyp (AP) (18%) and Invasive Fungal Sinusitis-Mucormycosis (17%). Mucormycosis was found in patients who have recovered from COVID along with a steroid intake history or had diabetes mellitus or had multiple comorbidities along with COVID recovery and steroid intake. Conclusion: Among the non-neoplastic lesion, IP is the most common lesion followed by AP. The significant number of mucormycosis cases was seen due to the ongoing COVID pandemic and liberal use of corticosteroids in the treatment.